Pilot scale sulfur dioxide-ethanol-water fractionation of recycled wood to sugars, bioethanol, lignin and lignosulfonates: Carbohydrate balance. (July 2020) - Iakovlev, Mikhail; Survase, Shrikant; Hill, Lee; Sideri, Stamatina; Rouzinou, Sofia; Kroff, Pablo; Pylkkanen, Vesa; Rutherford, Steve; Retsina, Theodora
Highlights: Waste wood is converted to sugars and ethanol on a pilot scale with SO2 -ethanol-water. SO2 -ethanol-water pretreatment of waste wood results in high sugar yields. Pilot scale sugar yields matched earlier laboratory scale results. Abstract: Two grades of recycled wood (Waste Wood A and Waste Wood B) were fractionated on a pilot scale (800 BD kg) to monomeric sugars, lignin and lignosulfonates using SO2 -Ethanol-Water (AVAP®) technology, including pretreatment, separation of cellulosic and hemicellulosic streams, and saccharification. Carbohydrate mass balance was obtained through determination of poly-, oligo- and monosaccharides as well as sugar degradation products in process streams. High monosaccharide yields were obtained confirming laboratory scale findings. Fermentability of mixed cellulosic and hemicellulosic sugar stream was confirmed on bench scale (25 kg).